Opferstatus und Geschlecht Entwicklung und Umsetzung der Opferhilfe in der Schweiz - Kersten, Anne (Differenzen, 2015)
Victim status and gender Development and implementation of victim assistance in Switzerland In Switzerland, the Victim of Crime Act (VCA; Opferhilfegesetz, OHG), in place since 1993, guarantees free legal, medical, psychological and social counselling, as well as some financial compensation for victims of violence. Although female and male persons are affected by violence to a comparable extent, male victims of violence are clearly underrepresented in victim support. How can this difference be explained? Do experiences of violence make women victims and not men? The author explores these questions. She reconstructs the emergence and implementation of state victim assistance in Switzerland from 1978-‐2011, working out how victim status is created in a process of social negotiation and what gender-‐ cultural practices are involved. The study offers broad insights into the nationwide political and media discourse surrounding the creation and design of the VCA as well as comparative case analyses of the implementation of the VCA in the cantons of Basel-‐Stadt/Basel-‐Landschaft and Bern.